2020
DOI: 10.1001/jamanetworkopen.2020.10478
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombosis Among Critically Ill Patients With Coronavirus Disease 2019 (COVID-19)

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2) was identified as a new coronavirus causing pneumonia and acute respiratory distress syndrome. It has become a pandemic, spreading particularly quickly across Europe and the US. Most deaths are related to severe acute respiratory distress syndrome, but other organ failures, such as acute kidney failure and acute cardiac injury, seem also related to the disease. 1 Inflammatory response is highly increased in coronavirus disease 2019 (COVID-19) infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
254
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(276 citation statements)
references
References 7 publications
14
254
0
3
Order By: Relevance
“…Data regarding VTE rate outside the ICU are more limited, but also suggest a possibly increased rate (range 3% to 6%) [ 16 , 25 ]. Other studies focused on Covid-19 patients also show a higher rate of DVT (65–69% in ICU patients [ 26 , 27 ], 11.9–21% in general ward patients [ 9 , 28 , 29 ]). Unlike what has been described by other authors [ 9 , 28 ], in our study most DVTs were proximal (84.6%) and only 15.4% of DVTs were distal.…”
Section: Discussionmentioning
confidence: 86%
“…Data regarding VTE rate outside the ICU are more limited, but also suggest a possibly increased rate (range 3% to 6%) [ 16 , 25 ]. Other studies focused on Covid-19 patients also show a higher rate of DVT (65–69% in ICU patients [ 26 , 27 ], 11.9–21% in general ward patients [ 9 , 28 , 29 ]). Unlike what has been described by other authors [ 9 , 28 ], in our study most DVTs were proximal (84.6%) and only 15.4% of DVTs were distal.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, a study with a short follow-up period also reported the existence of a dynamic correlation between the D-dimer levels and the severity of COVID-19 72 . Furthermore, pulmonary embolism and deep vein thrombosis were also observed in patients with severe COVID-19 73 , 74 , which suggests that D-dimer might play a prominent role in governing the severity of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Given that thrombo‐inflammation is the emerging basis of COVID‐19 coagulopathy, it is possible that the immunosuppressive effects of active cancer and cancer directed therapies modulated the thrombo‐inflammatory response. Prior reports of thrombotic events in hospitalized patients included a limited number of cancer patients with severe COVID‐19, which limits extrapolation 26,27 . In a retrospective series from Italy, there were only two patients with active cancer requiring ICU‐level care 28 .…”
Section: Discussionmentioning
confidence: 99%